Asuhan Keperawatan pada Ibu Hamil yang Mengalami Defisit Pengetahuan dengan Indikasi Kurangnya Informasi Metode KB di RSUD dr. Chasbullah Abdulmadjid - Azizah, Nur; Elwindra, Elwindra; Umar, Ahmad Farid (STIKes Persada Husada Indonesia, 2024)
Pregnancy is a physiological process that brings changes to the mother and her environment. The aim of this research is to determine nursing care for pregnant women who experience a knowledge deficit with indications of a lack of information on family planning methods carried out on 28 March - 10 May 2024. This research uses qualitative research methods at RSUD dr. Chasbullah Abdulmadjid Bekasi City. From the nursing care provided, 5 diagnoses were found in Mrs. W, namely knowledge deficit related to lack of exposure to information, hypovolemia related to active fluid loss, risk of injury to the fetus related to multiple parity, risk of injury to the mother related to contraction problems, and impaired comfort related to pain. To Mrs. M, namely knowledge deficit related to lack of exposure to information, hypovolemia related to active fluid loss, risk of injury to the fetus related to high parity, impaired comfort related to pain, and risk of nutritional deficit related to inability to digest food. At the evaluation stage of the 5 diagnoses, Mrs. W Mrs. M obtained resolved results according to the results criteria. 3x24 hours providing health education about family planning can overcome the problem. It is hoped that patients and partners can consider using birth control to reduce the risk of death for the mother and fetus.